2005
DOI: 10.1063/1.2114808
|View full text |Cite
|
Sign up to set email alerts
|

Development of a cooled He*(2S3) beam source for measurements of state-resolved collision energy dependence of Penning ionization cross sections: Evidence for a stereospecific attractive well around methyl group in CH3CN

Abstract: A low-temperature discharge nozzle source with a liquid-N(2) circulator for He*(2(3)S) metastable atoms has been developed in order to obtain the state-resolved collision energy dependence of Penning ionization cross sections in a low collision energy range from 20 to 80 meV. By controlling the discharge condition, we have made it possible to measure the collision energy dependence of partial ionization cross sections (CEDPICS) for a well-studied system of CH(3)CN+He*(2(3)S) in a wide energy range from 20 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…As described previously, 30 the OE method is able to describe effectively anisotropic potentials by expanded terms using overlap integrals between target MOs φ i and an atomic orbital χ. The expansion coefficients C i in eq 5 and the exponent ζ in eq 6 are parameters to be optimized in the potential corrections; however, in our previous studies [30][31][32][33] the optimized values of ζ in eq 6 have been found to be very close to the exponent of the 2s orbital of He* atom, which is 0.575 bohr -1 determined by Slater's rule. According to this fact, the parameter of ζ was fixed at the above value.…”
Section: Calculationsmentioning
confidence: 80%
See 4 more Smart Citations
“…As described previously, 30 the OE method is able to describe effectively anisotropic potentials by expanded terms using overlap integrals between target MOs φ i and an atomic orbital χ. The expansion coefficients C i in eq 5 and the exponent ζ in eq 6 are parameters to be optimized in the potential corrections; however, in our previous studies [30][31][32][33] the optimized values of ζ in eq 6 have been found to be very close to the exponent of the 2s orbital of He* atom, which is 0.575 bohr -1 determined by Slater's rule. According to this fact, the parameter of ζ was fixed at the above value.…”
Section: Calculationsmentioning
confidence: 80%
“…In the occupied MOs, the coefficients C i except for C 2 show positive values. As discussed in the previous studies, [30][31][32][33] contributions of the positive coefficients for occupied MOs supplement 2s-2p hybridization effects, 21,[57][58][59] which are underestimated in the Li model potential V 0 due to the larger energy gap between the 2s and 2p orbitals of the Li atom (1.848 eV) than that of He*(2 3 S) (1.114 eV). The relatively large negative value (-1195 meV) of the optimized coefficient C 2 is somewhat confusing; however, it is supposed that this feature is caused by a subtle balance of many factors in evaluating highly anisotropic interaction as the present system.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations